Mesenchymal stromal cell extracellular vesicles for multiple sclerosis in preclinical rodent models: A meta-analysis - Xun, Chengfeng; Deng, Huiyin; Zhao, Jing; Ge, Lite; Hu, Zhiping (Frontiers in Immunology, 2022)
Introduction Extracellular vesicles (EVs), especially mesenchymal stem (stromal) cell-derived EVs (MSC-EVs), have gained attention as potential novel treatments for multiple sclerosis (MS). However, their effects remain incompletely understood. Thus, the purpose of this meta-analysis was to systematically review the efficacy of MSC-EVs in preclinical rodent models of MS. Methods We searched PubMed, EMBASE, and the Web of Science databases up to August 2021 for studies that reported the treatment effects of MSC-EVs in rodent MS models. The clinical score was extracted as an outcome. Articles were peer-reviewed by two authors based on the inclusion and exclusion criteria. This meta-analysis was conducted using Stata 15.1 and R. Results A total of twelve animal studies met the inclusion criteria. In our study, the MSC-EVs had a positive overall effect on the clinical score with a standardized mean difference (SMD) of -2.17 (95% confidence interval (CI)):-3.99 to -0.34, P = 0.01). A significant amount of heterogeneity was observed among the studies. Conclusions This meta-analysis suggests that transplantation of MSC-EVs in MS rodent models improved functional recovery. Additionally, we identified several critical knowledge gaps, such as insufficient standardized dosage units and uncertainty regarding the optimal dose of MSC-EVs transplantation in MS. These gaps must be addressed before clinical trials can begin with MSC-EVs.